2013
DOI: 10.1071/fp12206
|View full text |Cite
|
Sign up to set email alerts
|

Can elevated CO2 combined with high temperature ameliorate the effect of terminal drought in wheat?

Abstract: Wheat (Triticum aestivum L.) production may be affected by the future climate, but the impact of the combined increases in atmospheric CO2 concentration, temperature and incidence of drought that are predicted has not been evaluated. The combined effect of elevated CO2, high temperature and terminal drought on biomass accumulation and grain yield was evaluated in vigorous (38–19) and nonvigorous (Janz) wheat genotypes grown under elevated CO2 (700 µL L–1) combined with temperatures 2°C, 4°C and 6°C above the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 56 publications
2
43
0
Order By: Relevance
“…Most previous studies on the impact of eCO 2 associated with drought and/or elevated temperature did not report whole ecosystem responses, but primarily plant responses at various organizational levels. Generally, they show that eCO 2 alleviates the stress associated with drought and/or elevated temperature (4,16,18,(22)(23)(24)(25)(26)(27)(28), but some studies found inconsistent responses (29)(30)(31)(32)(33)(34)(35)(36). This variability could be linked with the seasonality of precipitation (35,37) or with the intensity and length of the imposed stress, because the effect of eCO 2 has been shown to be positive under moderate drought and negligible under severe stress when stomata are fully closed (14).…”
Section: Resultsmentioning
confidence: 99%
“…Most previous studies on the impact of eCO 2 associated with drought and/or elevated temperature did not report whole ecosystem responses, but primarily plant responses at various organizational levels. Generally, they show that eCO 2 alleviates the stress associated with drought and/or elevated temperature (4,16,18,(22)(23)(24)(25)(26)(27)(28), but some studies found inconsistent responses (29)(30)(31)(32)(33)(34)(35)(36). This variability could be linked with the seasonality of precipitation (35,37) or with the intensity and length of the imposed stress, because the effect of eCO 2 has been shown to be positive under moderate drought and negligible under severe stress when stomata are fully closed (14).…”
Section: Resultsmentioning
confidence: 99%
“…Dias de Oliveira et al (2013) showed wheat responses to combined elevated CO 2 and temperatures +2°C, +4°C and +6°C above ambient, but did not identify the main driver for biomass and grain yield response or explain the interaction between the drivers of climate…”
Section: Introductionmentioning
confidence: 86%
“…Reviews by Ainsworth et al (2008), Tausz et al (2011) or Ziska et al (2012 reinforce the suggestion to explore breeding opportunities especially for elevated [CO 2 ]. Despite high profile papers and active research in the field, such as reported in Hasegawa et al (2013), Thilakarathne et al (2013), Dias de Oliveira et al (2013) or Bourgault et al (2013) in this volume, elevated [CO 2 ] effects are, in contrast to factors such as high and low temperatures, water supply and salinity, not yet included in current breeding efforts.…”
mentioning
confidence: 99%
“…Moreover, the increased severity and duration of heat waves, coupled with higher evapotranspiration, are likely to decrease soil moisture. In a study relevant to these probable scenarios, Dias de Oliveira et al (2013) Vandergeer et al (2013) showed that cassava yields and quality are sensitive to drought.…”
mentioning
confidence: 99%
See 1 more Smart Citation